Development of feeding information for infants with CHD. (5th August 2019) - Marino, Luise V.; Johnson, Mark J.; Davies, Natalie J.; Kidd, Catherine; Richens, Trevor; Bharucha, Tara; Darlington, Anne-Sophie
Abstract: Introduction: Infants with CHD often experience growth failure. Ensuring optimal growth before surgery is associated with improved outcomes and has emerged as a significant cause of parental stress. Parents have reported a perceived lack of accessible feeding information for infants with CHD. To address this gap, the aim of this study was to develop feeding information to better support parents. Materials and methods: A search for existing material on six electronic databases and an internet search for unpublished (grey) literature on feeding information for infants with CHD were carried out. Following the development of feeding information, semi-structured interview(s) with parents/health-care professionals were completed, focusing on whether the information was easy to understand, relevant, provided sufficient information around feeding/feeding difficulties, and whether there were any information gaps. Iterative changes were made to the information following each interview. The process was completed until thematic saturation was achieved. Results: A total of 23 unique articles were identified of which 5 studies were included. From the grey literature, four web pages were reviewed. A total of 22 parents and 25 health-care professionals were interviewed. All parents/health-care professionals felt that the feeding information developed provided sufficient information; however, many wanted information on how to introduce complementary food, particularly if weaning was delayed. Conclusions: This study describes the development of feeding information for infants with CHD. From parent interviews, gaps identified focused on the introduction of complementary foods and uncertainty regarding the feeding journey beyond surgery.